Popliteal vein aneurysm – Rare cause of knee pain - Hanin Al Douhani; Edwin Stephen; Ibrahim Abdelhady; Hanan Maawali; Khalifa AlWahaibi (Indian Journal of Vascular and Endovascular Surgery, 2023)
Despite the small number of reported cases of venous aneurysms, popliteal venous aneurysms (PVAs) are a potential source of venous thromboembolism (VTE) that carries significant morbidity and mortality. Recurrent VTE is a potential complication in cases of undiagnosed PVA. The knowledge of diagnosis and management of PVAs is limited among health professionals. The goal of this case report was to present the symptoms, diagnosis, and surgical management of PVA.